2007
DOI: 10.1302/0301-620x.89b9.19697
|View full text |Cite
|
Sign up to set email alerts
|

Should follow-up of patients with arthroplasties be carried out by general practitioners?

Abstract: Due to economic constraints, it has been suggested that joint replacement patients can be followed up in primary care. There are clinical, ethical and academic reasons why we must ensure that our joint replacements are appropriately clinically and radiologically followed up to minimise complications. This Editorial discusses this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 3 publications
3
16
0
1
Order By: Relevance
“…22 Spiralling health-care costs may force a decrease in the length of follow-up after a THR with the results that asymptomatic loosening is not identified at an early stage with an increase in risk of subsequent fracture. 23 Our results confirm the reliability and reproducibility of the Vancouver classification system. In addition, we have shown that substantial agreement can be found between individuals with no specialist training.…”
Section: Discussionsupporting
confidence: 81%
“…22 Spiralling health-care costs may force a decrease in the length of follow-up after a THR with the results that asymptomatic loosening is not identified at an early stage with an increase in risk of subsequent fracture. 23 Our results confirm the reliability and reproducibility of the Vancouver classification system. In addition, we have shown that substantial agreement can be found between individuals with no specialist training.…”
Section: Discussionsupporting
confidence: 81%
“…Hacking et al33 performed a prospective analysis of 110 THAs over a four-year period, and they found that only four (3.6%) of the 110 cases were for asymptomatic revisions in the first seven years after primary THA. Other studies supported “no follow-up” until several years after primary THA 58,59. The findings in the present study corroborated these results.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, revision surgery constitutes 12% of all hip arthroplasty procedures in the National Joint Registry, the largest group constituting those undertaken for aseptic loosening or osteolysis (National Joint Registry, 2013). These conditions are often silent at onset and, if undetected, may lead to substantial loss of bone with subsequent peri-prosthetic fracture and a significantly higher cost of revision than for aseptic loosening alone (Haddad et al, 2007;Ghoz and Macdonald, 2008;Huddleston et al, 2010). This situation is more challenging for the orthopaedic surgeon and is associated with a higher risk for the patient (Paprosky et al, 2001;Barrack, 2004;Howard, 2009;Vanhegan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%